2017
DOI: 10.1002/srin.201700071
|View full text |Cite
|
Sign up to set email alerts
|

Review on Modeling and Simulation of Blast Furnace

Abstract: The design and control of blast furnace (BF) ironmaking must be optimized in order to be competitive and sustainable, particularly under the more and more demanding and tough economic and environmental conditions. To achieve this, it is necessary to understand the complex multiphase flow, heat and mass transfer, and global performance of a BF under different conditions. Mathematical modeling, often coupled with physical modeling, plays an important role in this area. This paper reviews the recent developments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(72 citation statements)
references
References 174 publications
(407 reference statements)
0
72
0
Order By: Relevance
“…The behavior of burden descent in the BF has been studied extensively and intensively in the literature [1,3,6,11,12,[27][28][29][30][31]. The path lines of the solid in the BF can be generally assumed as depicted in Figure 2, where plug flow is the main solid flow pattern in the upper and middle zones (i.e., lumpy zone), while a slight convergent flow and a dead man zone dominate in the lower bosh zone.…”
Section: Burden Layer Descentmentioning
confidence: 99%
See 2 more Smart Citations
“…The behavior of burden descent in the BF has been studied extensively and intensively in the literature [1,3,6,11,12,[27][28][29][30][31]. The path lines of the solid in the BF can be generally assumed as depicted in Figure 2, where plug flow is the main solid flow pattern in the upper and middle zones (i.e., lumpy zone), while a slight convergent flow and a dead man zone dominate in the lower bosh zone.…”
Section: Burden Layer Descentmentioning
confidence: 99%
“…As a consequence, most of the studies on the conditions of the burden in the lumpy zone have been based on laboratory-scale experiments or mathematical modeling. Such studies have, e.g., [3][4][5], presented correlations between the charging pattern and the burden structure in the lumpy zone. However, since direct measurements of the layers in the shaft are lacking, the modeling results have usually only been verified for the top layers in the throat or indirectly through gas temperature and composition measurements in the throat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of mixed layers is a significant phenomenon in a BF because the porosity at the interface regions is of major importance in the definition of nonuniform flow through the stack region of a BF. Laboratory‐scale experiments, scaled burden descent models as well as industrial measurements have been conducted to examine mixed layer formation. These studies revealed that the mixed layer usually has much lower gas permeability compared with the individual layers.…”
Section: Introductionmentioning
confidence: 99%
“…Such task is to be solved based on development and application of new methods and algorithms [1][2][3][4][5]. The mathematical models of technical processes and production [6][7][8] represent the intellectual core of such system.…”
Section: Introductionmentioning
confidence: 99%